PERAN PENYULUH PERTANIAN PADA PETANI PADI SAWAH DI DESA RADEY KECAMATAN TENGA KABUPATEN MINAHASA SELATAN (The Role Of Agricultural Extender On Rice Farmers In Radey Village, Tenga Sub District, South Minahasa Regency) - Andhika Mandagi; Melsje J. Memah; Jane S. Tambas (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to know the role of agricultural extender on rice farmers in Radey Village, Tenga Sub district South Minahasa Regancy. Research was conducted in August to December 2021, with the data used comes from primaery and secondary data and is then descrypted.The research result showed that know the role of agricultural extender on rice farmers in Radey Village, Tenga Sub district South Minahasa Regancy is less work because the amount of extender is less, extenders are less able to explain to rice farmers and the number of extender is only one person handling all farming in Radey Village and also not staying in Radey Village.